Characterization and functional analysis of serpin-1 like gene from oak silkworm Antheraea pernyi. Issue 5 (23rd February 2017) - Yu, H.M.; Zhu, B.J.; Sun, Y.; Wei, G.Q.; Wang, L.; Qian, C.; Nadeem Abbas, M.; Liu, C.L.
Abstract: Serpins are a broadly distributed family of proteases found in various organisms that play an important role in regulating the immune response. Here, we identified a serpin-1 gene from Antheraea pernyi that encodes a 279 amino acid protein with a molecular weight of 30.8 kDa. We expressed the recombinant Ap-serpin-1 protein in Escherichia coli and used the purified protein to prepare rabbit anti-Ap-serpin-1 polyclonal antibodies. We calculated the enzyme-linked immunosorbent assay titer of the antibody as 1:128000. Quantitative real-time polymerase chain reaction analysis revealed that Ap-serpin-1 was expressed in all examined tissues, including hemolymph, malpighian tubules, midgut, silk gland, integument and the fat body; the highest Ap-serpin-1 expression levels was detected in the fat body. We next investigated the expression patterns of Ap-serpin-1 in both fat body and hemolymph samples, following treatment with E. coli, Beauveria bassiana, Micrococcus luteus and nuclear polyhedrosis virus (NPV). We reported that NPV and M. luteus significantly enhanced Ap-serpin-1 expression in the fat body. While, in the hemolymph samples, treatment with B. bassiana and M. luteus was shown to upregulate Ap-serpin-1 expression at 24 h induction. Altogether, our results suggest that Ap-serpin-1 is involved in the innate immunity of A. pernyi .